Exploring relations between traffic accidents and business productivity using system dynamics - Duarte Forero, Edgar Leonardo; Camacho Oliveros, Manuel Ángel; Meneses Velosa, Sonia (Scientia et Technica, 2018)
Traffic accidents are commonly analyzed considering three main factors: driver’s behavior, car’s conditions, and the roads conditions. An exploration of the relations among business productivity and traffic accidents is made, considering also the influence of traffic authorities. A simulation model based on System dynamics was developed to explore the specific relations among the behavior of drivers and the working pressure of their jobs, and the traffic controls made by government authorities. The analysis considers that an improvement in productivity and a fewer, but more intense traffic controls, is a valid strategy to reduce accidents in roads. The model is a useful tool that can be applied in the design of public policies for road safety